Pemahaman Konseptual dan Prosedural Siswa SMA/MA dalam Menyelesaikan Soal Program Linier Berdasarkan Tipe Kepribadian - Risky Armanza; Beni Asyhar (Jurnal Tadris Matematika, 2020)
This study aimed to describe the conceptual and procedural comprehension to solve linear program story problems in students who are an extrovert and an introvert. This was qualitative study with a case study method. The subjects were two students who are an extrovert and an introvert. Data collection included personality questionnaires, question tests, and interviews. Validity test of the data used time triangulation. Data analysis was conducted based on indicators of conceptual and procedural comprehension, which include data reduction, data presentation, and conclusion drawing. The results showed that the extroverted subject was able to meet all indicators of conceptual and procedural comprehension. This was reflected from the way the subject solved the questions properly according to the existing procedures. In contrast, the introverted student was also able to meet the procedural comprehension indicators, but did not meet the conceptual comprehension indicator. This was reflected from the mistakes that the subject made in comprehending the questions and the errors in interpreting the questions into mathematical model.